Risk factors for healthcare associated infections and in-hospital mortality in neurological intensive care unit in tertiary hospital in Belgrade, Serbia: A prospective cohort study - Vidaković Stefan; Raičević Ranko; Grunauer Marija; Pasovski Viktor; Šuljagić Vesna (Vojnosanitetski Pregled)
Background/Aim. Patients in a neurologic intensive care unit (ICU) are especially susceptible to healthcare-associated infections (HAIs). HAIs are cause of significant morbidity and mortality. Aim of this study was to assess the incidence of HAIs, to identify significant risk factors (RFs) and causative microorganisms for HAIs and to identify RFs for inhospital mortality in a neurological ICU. Methods. A prospective cohort study was conducted in the six-bed ICU of the Clinic for Neurology, Military Medical Academy in Belgrade from January 1, 2014 to December 31, 2016. Active surveillance on HAIs was performed by the hospital infection control team, using methodologies of the European Centre for Disease Prevention and Control and the National Healthcare Safety Network/Centres for Disease Prevention and Control. Results. One hundred forty eight patients with a total of 2,708 patient-days were enrolled. There were 49 HAIs in 39 patients during the study period. The incidence and incidence density of HAIs were 26.3% and 18.1 per 1000 patient-days, respectively. The most frequent HAIs were urinary tract infections (15.5%), pneumonia (10.1%) and bloodstream infections (4%). RFs independently associated with HAIs in the neurological ICU were: urinary catheter [risk ratio (RR): 5.6; 95% confidence interval (CI): 1.153–27.632], urinary catheter-days (RR: 1.1; 95% CI: 1.057–1.188), central-line days (RR: 1.1; 95% CI: 1.010– 1.150), and mechanical ventilation (RR: 0.3; 95% CI: 0.079– 0.859). The most common microorganism was Klebsiella spp. RFs independently associated with in-hospital mortality in the neurological ICU were: mechanical ventilation (RR: 6.5; 95% CI: 2.868–14.116), Glasgow Coma Score (RR: 2.7; 95% CI: 1.135–6,396), and age (RR: 1.03; 95% CI: 1.005– 1.055). Conclusion. Usage of invasive procedures during ICU hospitalization carries significant risk for development of HAIs. HAIs in ICU setting are most often caused by Gram-negative bacteria with substantial antimicrobial resistance. These results stress the importance of infection prevention.